2022
DOI: 10.1002/jmv.28029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of response to different COVID‐19 vaccines in vaccinated healthcare workers in a single center in Iran

Abstract: Due to the recent coronavirus disease 2019 (COVID-19) pandemic and emergent administration of various vaccines worldwide, comprehensive studies on the different aspects of vaccines are in demand. This study evaluated antibody response after the second dose of the COVID-19 vaccine in the Children's Medical Center personnel. The blood samples of 174 healthcare workers were gathered at least 10 days after vaccination. The administered vaccines included Oxford/AstraZeneca, COVAXIN, Sinopharm, and Sputnik V. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
(76 reference statements)
2
8
0
Order By: Relevance
“…A study by Pourakbari and colleagues found a pediatric mortality rate of 10%. 24 In the current study, as with others, an underlying medical condition appears to be a key factor in determining COVID-19 disease in children, but there is a lack of evidence to judge the importance and strength of our findings; therefore, it suggests more research. 25 The small sample size of our study is a main limitation, especially the sample size of patients with SARS-CoV-2 viremia, which may affect the statistical results.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…A study by Pourakbari and colleagues found a pediatric mortality rate of 10%. 24 In the current study, as with others, an underlying medical condition appears to be a key factor in determining COVID-19 disease in children, but there is a lack of evidence to judge the importance and strength of our findings; therefore, it suggests more research. 25 The small sample size of our study is a main limitation, especially the sample size of patients with SARS-CoV-2 viremia, which may affect the statistical results.…”
Section: Discussionmentioning
confidence: 48%
“…However, the current study reports only two deaths (4%) in infants with a complicated underlying medical condition. A study by Pourakbari and colleagues found a pediatric mortality rate of 10% 24 …”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have applied the ELISA to detect neutralizing antibodies, and the data suggested that using RBD as an immunogen might be a better strategy for creating a robust neutralization Ab response compared with full-length S protein 50 , and the ELISA results were highly responsive to neutralizing antibody levels 51 .…”
Section: The Persistence Of T-cell Immunity Stimulated By Sars-cov-2 ...mentioning
confidence: 99%
“…Although various studies have been carried out to investigate the immunogenicity and reactogenicity of COVID-19 vaccines in various populations, 25 27 the efficacy and adverse events of these vaccines in the Iranian population are not well identified so far. Therefore, the aim of this study was to investigate whether the Oxford-AstraZeneca- and Sinopharm vaccines, as the most frequent vaccines used in the national vaccination protocols, had immunogenicity and side effects in healthy individuals and patients with autoimmune disorders in Kashan, Iran.…”
Section: Introductionmentioning
confidence: 99%